PENGARUH LIFESTYLE MARKETING MIX TERHADAP KEPUTUSANPEMBELIAN DAN KEPUASAN KONSUMEN SEPEDA MOTOR SPORT250CC DI KOTA PEKANBARU - Masikah, Atikah; Alwie, Alvi Furwanti; Sulistyowati, Lilis (Jurnal Tepak Manajemen Bisnis, 2016)
This study aimed to analyze the influence Lifestyle MarketingMix (Luxury, Indulgence, Self â Concept, and Admired) Towards MotorcycleSport 250cc Purchase Decision and Customer Satisfaction In Pekanbaru. Thisstudy using cencus with all 120 members Independen Ninja Club Rider and RiauCBR Club being sampled. Data was collected by giving questionnaires to themembers Independen Ninja Club Rider and Riau CBR Club. Data that beingcollected is analyse using PATH by SPSS version 22Research results shows thathigh Self â Concept increasing Purchase Decision, but low Luxury, Indulgence,and Admire lowering Purchase Decision on 250cc Sports Motorcycle. PurchaseDecision positively mediated the Influence of Luxury, Indulgence, Self â Concept,and Admire, toward 250cc Sports Motorcycle Customer Satisfaction. Eventhough,Luxury, Indulgence, had low influence toward 250cc Sports Motorcycle CustomerSatisfaction, but Self â Concept and Admire had high Influence toward 250ccSports Motorcycle Customer Satisfaction.